The physiological requirements of and nutritional recommendations for equestrian riders - Best, R.; Williams, J. M.; Pearce, J. (Nutrients, 2023)
Equestrian sport is under-researched within the sport science literature, creating a possible knowledge vacuum for athletes and support personnel wishing to train and perform in an evidence-based manner. This review aims to synthesise available evidence from equitation, sport, and veterinary sciences to describe the pertinent rider physiology of equestrian disciplines. Estimates of energy expenditure and the contribution of underpinning energy systems to equestrian performance are used to provide nutrition and hydration recommendations for competition and training in equestrian disciplines. Relative energy deficiency and disordered eating are also considered. The practical challenges of the equestrian environment, including competitive, personal, and professional factors, injury and concussion, and female participation, are discussed to better highlight novelty within equestrian disciplines compared to more commonly studied sports. The evidence and recommendations are supported by example scenarios, and future research directions are outlined.